2016
DOI: 10.1103/physrevb.93.024508
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure of the titanium-based oxypnictide superconductorBa0.95Na0.05Ti2Sb2Oand direct observation of its char

Abstract: Ba 0.95 Na 0.05 Ti 2 Sb 2 O is a titanium-based oxypnictide superconductor with possible density wave order. We have performed high resolution angle-resolved photoemission spectroscopy (ARPES) and scanning tunneling microscopy (STM) studies on Ba 0.95 Na 0.05 Ti 2 Sb 2 O. Our STM studies find a charge density wave (CDW) order with the wavevector of (π, π). The electronic structure shows both multi-orbital and three-dimensional nature, consistent with the theoretical calculations. The observed Fermi surfaces ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 19 publications
2
4
0
Order By: Relevance
“…To account for the results, intra-unit-cell nematic charge order was proposed, such as that proposed in cuprates [58,59]. Recently, Song et al reported direct observation of the CDW order with the wave vector of (π, π) by STM measurements on Ba0.95Na0.05Ti2Sb2O (Figure 16), which is consistent with that theoretically predicted by Subedi and Nakano et al [46]. They also performed ARPES measurements and revealed the Fermi surface is well nested along the (π, π) direction, which is consistent with STM study, suggesting the electron-phonon mediated superconductivity in Ba0.95Na0.05Ti2Sb2O.…”
Section: The Dw Instability In Bati 2 Pn 2 Osupporting
confidence: 77%
See 1 more Smart Citation
“…To account for the results, intra-unit-cell nematic charge order was proposed, such as that proposed in cuprates [58,59]. Recently, Song et al reported direct observation of the CDW order with the wave vector of (π, π) by STM measurements on Ba0.95Na0.05Ti2Sb2O (Figure 16), which is consistent with that theoretically predicted by Subedi and Nakano et al [46]. They also performed ARPES measurements and revealed the Fermi surface is well nested along the (π, π) direction, which is consistent with STM study, suggesting the electron-phonon mediated superconductivity in Ba0.95Na0.05Ti2Sb2O.…”
Section: The Dw Instability In Bati 2 Pn 2 Osupporting
confidence: 77%
“…These predicted FS of BaTi2Pn2O is highly similar to that theoretically predicted in Na2Ti2Pn2O [25,32,45]. Experimentally, Song et al recently performed angle-resolved photoemission spectroscopy (ARPES) studies on Ba0.95Na0.05Ti2Sb2O single crystals and found the multiband electronic structure having electron and hole pockets, consistent with the theoretical studies [46]. …”
Section: Electronic Structure Of Bati2pn2osupporting
confidence: 65%
“…The perpendicular δ and ε pockets in Figs. 2(c-f) are from two inequivalent X points (X 2 and X 1 , in blue), and appear together due to the poor k z resolution of our experiments using vacuum ultraviolet photons (VUV-ARPES) -the bands from a specific k z plane may have a projection over a wide range of k z 46,47 . Meanwhile, the X 3 point (beige) is projected to the Γ point for the same reason.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, Song et al has very recently reported the existence of (1/2, 1/2) nesting vector by ARPES and STM measurements applied to high-quality single crystals, being consistent with the theoretical predictions. [26] The superlattice structure is hence expected to be detected by further diffraction measurements. The theoretically estimated distortion here is quite small, 0.14 Å (See Supplementary Note 4), being in agreement with the previous calculation by Subedi, [15] so careful detections would be required for experiments.…”
Section: Discussion Comparison With Experimentsmentioning
confidence: 99%
“…Indeed, such shapes have been recently observed by state-of-the-art Angle-Resolved Photo Emission Spectroscopy (ARPES) applied to BaTi 2 As 2 O and BaTi 2 Sb 2 O single crystals. [25,26] Subedi [15] worked on BaTi 2 Sb 2 O using DFT and reported the possible lattice instability toward CDW with √ 2 × √ 2 × 1 superstructure at low temperature. Experimentally, however, no such superlattice peaks were found by neutron and electron diffractions for this compound, [17,27] reviving the argument over if the anoma-lies in ρ(T ) and χ(T ) can be really attributed to the phonondriven CDW or not.…”
mentioning
confidence: 99%